Evaluation of Clinical Practice of Anesthesiology Students Based on Self Assessment in Shahrekord University of Medical Sciences - M Delaram; A Zaheri; L Rafiee Vardanjani; Gh shabanian (Babol University of Medical Sciences, 2019)
BACKGROUND AND OBJECTIVE: In this analytical, cross-sectional study, 60 undergraduate anesthesia students of Medical Sciences Faculty of shahrekord that were selected by the census sampling method participated. For data collection, a two-part questionnaire including demographic characteristics and a 710-item evaluation was used. The validity of the questionnaire was determined through the face and content validity with the help of 10 professors and the reliability of this tool was measured 0.83, by calculating Cronbach's alpha coefficient. Data analysis was done using SPSS 16 software and descriptive statistics methods METHODS: The results of this study showed that the average age of participants was 21.73±0.85 years. In the courses of principles and methods of anesthesia, the principles of pain management, medical emergencies, intensive  care, the highest percentage of students' skill in transferring patients from the bed and stretcher69.8%, existing methods for control Chronic and acute pain, 13.2%, preparation of the tools and equipment needed to perform CPR8 / 80%, have the principles of airway clean up in critical cases 65.4%. FINDINGS: The results of this study showed that the average age of participants was 21.73±0.85 years. In the courses of principles and methods of anesthesia, the principles of pain management, medical emergencies, intensive  care, the highest percentage of students' skill in transferring patients from the bed and stretcher69.8%, existing methods for control Chronic and acute pain, 13.2%, preparation of the tools and equipment needed to perform CPR8 / 80%, have the principles of airway clean up in critical cases 65.4%. CONCLUSION: Anesthesia students have evaluated their skills in high-level at anesthetic principles and moderate in intensive care course and less in pain management lessons. It is suggested that in the future studies this method of evaluation is compared with other methods.